Pengaruh Persepsi Kualitas Produk, Persepsi Promosi Harga (Tanggal Kembar), Dan Buy Now Pay Later Terhadap Pembelian Impulsif Produk Wardah Di Shopee (Studi pada Mahasiswi Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Malang Angkatan 2022) - Utami, Nita Ani Dia; Primanto, Alfian Budi; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This research seeks to analyze the influence of perceived product quality, price promotions through double-date campaigns, and the buy now pay later payment option on impulsive buying behavior toward Wardah products on the Shopee platform. The study adopts a quantitative research design using a survey approach. The population comprises female undergraduate students enrolled in the Management Study Program, Faculty of Economics and Business, Universitas Islam Malang, cohort of 2022. A purposive sampling technique was utilized, yielding 89 valid respondents. The collected data were processed using multiple linear regression analysis with the support of SPSS software. The results reveal that perceived product quality exerts a positive yet statistically insignificant impact on impulsive purchasing. Conversely, price promotions associated with double-date events and the buy now pay later facility show a positive and significant effect on impulsive buying behavior. When examined simultaneously, all independent variables exhibit a significant positive influence on impulsive purchasing decisions for Wardah products on Shopee. These findings highlight the importance of promotional mechanisms and flexible payment alternatives in encouraging impulsive purchasing within e-commerce settings. Keywords: Impulsive Buying. Perceived Product Quality. Price Promotion. Buy Now Pay Later.